Engineered Orange Ectopically Expressing the Arabidopsis β-Caryophyllene Synthase Is Not Attractive to Diaphorina citri, the Vector of the Bacterial Pathogen Associated to Huanglongbing - Alquézar, Berta; Volpe, Haroldo Xavier Linhares; Magnani, Rodrigo Facchini; de Miranda, Marcelo Pedreira; Santos, Mateus Almeida; Marques, Viviani Vieira; de Almeida, Márcia Rodrigues; Wulff, Nelson Arno; Ting, Hieng-Ming; de Vries, Michel; Schuurink, Robert; Bouwmeester, Harro; et al. (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is a destructive disease, associated with psyllid-transmitted phloem-restricted pathogenic bacteria, which is seriously endangering citriculture worldwide. It affects all citrus species and cultivars regardless of the rootstock used and, despite intensive research in the last decades, there is no effective cure to control either the bacterial species (Candidatus Liberibacter spp.) or their insect vectors (Diaphorina citri and Trioza erytreae). Currently, the best attempts to manage HLB are based on three approaches: (i) reducing the psyllid population by intensive insecticide treatments; (ii) reducing inoculum sources by removing infected trees and (iii) using nursery-certified healthy plants for replanting. The economic losses caused by HLB (decreased fruit quality, reduced yield and tree destruction) and the huge environmental costs of disease management seriously threaten the sustainability of the citrus industry in affected regions. Here, we have generated genetically modified sweet orange lines to constitutively emit -caryophyllene, a sesquiterpene repellent to Diaphorina citri, the main HLB psyllid vector. We demonstrate that this alteration in volatile emission affects behavioral responses of the psyllid in olfactometric and no-choice assays, making them repellent/less attractant to the HLB vector, opening a new alternative for possible HLB control in the field